The Influence of Assignments on the Mental Health of Student if the Department of Phisiscs Education, Yogyakarta State University, 2023: Pengaruh Tugas terhadap Kesehatan Mental Mahasiswa Departemen Fisika, Universitas Negeri Yogyakarta tahun 2023 - Fathira Oktavina, Siti; Hapsary, Yunni; Setiaji, Bayu (Borneo Educational Journal (Borju), 2024)
Having good mental health is something that everyone hopes for. The importance of mental health for students can control their emotion regarding the situation they are facing. However, students often complain that they feel like they have too much assignments. So that not many of them feel stressed and pressured in doing it. Therefore, it is important to study further regarding students’ mental health. This research aims to prove how much influence coursework has on the mental health of students in the Department of Physics Education, Yogyakarta State University in 2023. The research method used is quantitative with a descriptive analytical approach. The sample used was 85 students from the Department of Physics Education, Yogyakarta State University class of 2023 using total sampling. The analysis carried out was a normality test which showed that the data was not normally distributed so it was carried out using the Mann-Whitney non-parametric test. The research result that can be conclude are that the influence of student assignments is quite small on the mental health of students at the Department of Physics Education, Yogyakarta State University in 2023.